IMPLEMENTASI CULTURE EXPERIENCE DALAM PEMBELAJARAN IPAS BERBASIS ETHNOSCIENCE UNTUK MENUMBUHKAN KESADARAN BUDAYA PESERTA DIDIK DI KELAS IV SEKOLAH DASAR - niswatul azizah; Imanatun Fadhilah; Arinal Hikmah; Suci Herwani (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2025)
This study aims to analyze the role of culture experience in ethnoscience-based Integrated Science and Social Studies (IPAS) learning in fostering elementary students’ cultural awareness. A descriptive qualitative approach was employed involving IPAS teachers and fourth-grade students as research participants. Data were collected through observation, interviews, and documentation, and analyzed using Miles and Huberman’s model, including data reduction, data display, and conclusion drawing. Data credibility was ensured through source and technique triangulation. The findings indicate that the implementation of culture experience through local culture-based activities effectively integrates scientific concepts with cultural values in a contextual learning process. Ethnoscience-based IPAS learning plays a significant role in enhancing students’ conceptual understanding, learning engagement, and awareness of preserving local culture. These results suggest that culture experience is an effective approach to strengthening scientific literacy while fostering cultural awareness among elementary school students.